A Biomimetic Aggregation‐Induced Emission Photosensitizer with Antigen‐Presenting and Hitchhiking Function for Lipid Droplet Targeted Photodynamic Immunotherapy. Issue 33 (11th July 2021) - Xu, Xiuli; Deng, Guanjun; Sun, Zhihong; Luo, Yuan; Liu, Junkai; Yu, Xinghua; Zhao, Yang; Gong, Ping; Liu, Guozhen; Zhang, Pengfei; Pan, Fan; Cai, Lintao; et al.
Abstract: Photodynamic therapy (PDT) is a promising alternative approach for effective cancer treatment that is associated with an antitumor immune response. However, immunosuppression of the tumor microenvironment limits the immune response induced by PDT. Stimulation and proliferation of T cells is a critical step for generating immune responses and depends on the efficient presentation of tumor antigens and co‐stimulatory molecules by antigen‐presenting cells (APCs). Here, biomimetic aggregation‐induced emission (AIE) photosensitizers with antigen‐presenting and hitchhiking abilities (DC@AIEdots) are developed by coating dendritic cell (DC) membranes on the nanoaggregates of the AIEgens. Notably, the inner AIE molecules can selectively accumulate in lipid droplets of tumor cells, and the outer cell membrane can facilitate the hitchhiking of DC@AIEdots onto the endogenous T cells and enhance the tumor delivery efficiency by about 1.6 times. Furthermore, DC@AIEdots can stimulate the in vivo proliferation and activation of T cells and trigger the immune system. The potential applications of therapeutic agents targeting lipid droplets for immunotherapy are indicated and a new hitchhiking approach for drug delivery is provided. Lastly, the study presents a photoactive and artificial antigen‐presenting platform for effective T cell stimulation and cancer photodynamic immunotherapy. Abstract : Biomimetic aggregation‐induced emission (AIE) photosensitizers with antigen‐presenting and hitchhiking abilities (DC@AIEdots) are presented by coating dendritic cell (DC) membranes on AIE nanoaggregates. The inner AIE molecules can selectively accumulate in tumor cells, and the outer cell membrane facilitates DC@AIEdots hitchhiking on endogenous T cells, enhancing tumor delivery efficiency and stimulating T cell proliferation and activation in vivo.